Strategi Peningkatan Mutu Pendidikan Sekolah Dasar Islam Terpadu (SDIT) di Provinsi Kalimantan Timur (Studi kasus SDIT Cordova Samarinda dan SDIT YABIS Bontang) - Khairul Saleh; Lina Revilla Malik (FENOMENA, 2019)
Demands for graduates of quality educational institutions increasingly urgent, in addition to competition between educational institutions also educational institutions must meet minimum graduation standards. This study uses a qualitative approach using data collection techniques, observation, interviews and documentation. Based on the findings, the authors conclude as follows: Education Quality Improvement Strategies at SDIT Cordova Samarinda and SDIT YABIS Bontang in terms of the input strategy adopted, namely the selection of Human Resources through a rigorous selection process in accordance with specified criteria; procurement of public utilities and insfrastructures are very complete; partnership support through collaboration with school committees and related foundations and educational institutions; funding guarantees obtained from stakeholders and the integration of the national curriculum, integrated Islamic school network and foundation, In the aspects of the strategic process adopted, namely optimizing the process of decision making, institutional management processes, program management processes, teaching and learning processes, and monitoring and evaluation processes. With a note that the teaching and learning process has the highest level of importance compared to other processes. While increasing the output aspect taken is to improve academic achievement by optimizing existing components and strive to produce quality graduates and increase non-academic achievements by seeking to produce students who have Islamic characters and excel in the arts, sports and extracurricular fields.